Location-based analysis and optimization of service network performance: A case study - Yang, Shuo; Yu, Hao; Solvang, Wei Deng (2018 2nd International Symposium on Small-scale Intelligent Manufacturing Systems (SIMS), 2018)
Accepted manuscript file. Published version available at: https://doi.org/10.1109/SIMS.2018.8355296 The location problem of service network has been extensively focused by researchers in operational research due to the difficulty in balancing the level of service and efficiency. On the one hand, installing a large number of service facilities within the service network improves availability and responsiveness to customer demands, but it also increases the investment and operating cost. While on the other hand, opening a limited number of facilities in a service network increases the efficiency with a compromise of responsiveness and customers' satisfaction. In order to balance the level of service and efficiency of a service network, this paper defines three location-based performance indicators with respect to three locations models: availability (set covering location model), efficiency (maximal covering location model), and responsiveness (p-median location model). In order to illustrate a deep managerial insight of real-world application, a case study of postal service network in Narvik is performed latter in this paper.